Possibilities of economic progress - Youngson, A. J. (Cambridge, Eng. : University Press, 1959)
This book Is about Economic progress in a social and political situation, Human aptitude and skills, geographical situation and natural resources.
Includes bibliographical footnotes and index.
oo 12/08/2018
Loans
Keywords: Economic development